Measurement of left ventricular ejection fraction by acoustic quantification and comparison with radionuclide angiography - Yvorchuk, Kenneth J.; Davies, Ross A.; Chan, Kwan-Leung (The American journal of cardiology, 1994)
Left ventricular (LV) ejection fraction (EF) is an important measure of systolic function, with radionuclide angiography being the accepted standard for its determination. Echocardiography is ideal for repeated measurements of EF, but most methods are either subject to error in the presence of regional wall abnormalities or require cumbersome off-line analysis. Acoustic quantification is a recently introduced method that allows for the continuous on-line display of LV cavity dimensions, but the on-line algorithm for the measurement of EF has not been validated against an independent standard in the clinical setting. This study attempted to validate acoustic quantification in the determination of EF by comparison with off-line echocardiographic analysis and radionuclide angiography in 54 patients referred for this latter procedure. Acoustic quantification correlated well with offline analysis in both the apical 4-chamber (r = 0.89, n = 43) and 2-chamber (r = 0.86, n = 26) views. Similarly, it also correlated well with radionuclide angiography in the 4-chamber (r = 0.81, n = 44) and 2-chamber (r = 0.83, n = 26) views. The correlation between the 2 methods was further improved when only the last 30 patients were assessed (r = 0.91, n = 25 for 4-chamber views; r = 0.86, n = 16 for 2-chamber views). The correlation was worse in patients with regional asynergy (r = 0.69, n = 17 for 4-chamber views; r = 0.76, n = 10 for 2-chamber views). Moreover, acoustic quantification tended to underestimate EF when compared with radionuclide anglography. It is concluded that acoustic quantification is a promising technique for online determination of EF, but is limited by a lack of applicability in all patients, the presence of a learning curve, its inaccuracy in ventricles with regional asynergy, and its tendency to underestimate EF.